2022
DOI: 10.3390/molecules27196235
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Dihydropyridine and Pyridine Analogs as Potent Human Tissue Nonspecific Alkaline Phosphatase Inhibitors with Anticancer Activity: ROS and DNA Damage-Induced Apoptosis

Abstract: Small molecules with nitrogen-containing scaffolds have gained much attention due to their biological importance in the development of new anticancer agents. The present paper reports the synthesis of a library of new dihydropyridine and pyridine analogs with diverse pharmacophores. All compounds were tested against the human tissue nonspecific alkaline phosphatase (h-TNAP) enzyme. Most of the compounds showed excellent enzyme inhibition against h-TNAP, having IC50 values ranging from 0.49 ± 0.025 to 8.8 ± 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…In our study, LMS showed relatively low intercalation abilities, and only in high dosages (Supplemental Fig 3F ), making a direct intercalation mechanism in our experiments unlikely. Similarily to our data, the compound 4d, a synthetic manufactured metabolite of LMS, has been shown to induce cell-cycle arrest in HeLa cells and was found to induce DNA damage, although the direct mechanism remains unknown (66).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, LMS showed relatively low intercalation abilities, and only in high dosages (Supplemental Fig 3F ), making a direct intercalation mechanism in our experiments unlikely. Similarily to our data, the compound 4d, a synthetic manufactured metabolite of LMS, has been shown to induce cell-cycle arrest in HeLa cells and was found to induce DNA damage, although the direct mechanism remains unknown (66).…”
Section: Discussionsupporting
confidence: 90%
“…S4F), making a direct intercalation mechanism in our experiments unlikely. Similar to our data, the compound 4d, a synthetic manufactured metabolite of LMS, has been shown to induce cell-cycle arrest in HeLa cells and was found to induce DNA damage, although the direct mechanism remains unknown [63].…”
Section: Discussionsupporting
confidence: 88%
“…Permeability of the cell membrane has important physiological functions for the movement of water inside and outside the cell, the exchange of various substances, and the maintenance of pH and osmotic pressure [ 51 , 52 ]. To study the membrane permeability of the tested phytopathogenic bacteria affected by our designed compounds, the Xoo cells were detected by using a typical PI staining assay [ 53 ], in which the nonfluorescent dye PI can bind to DNA and RNA in cells with a damaged cell membrane and produce strong red fluorescence, but it cannot pass through cells with intact cell membranes, so the intensity and distribution of red fluorescence indirectly reflects the membrane permeability [ 54 ]. Clearly, the progressively elevated red fluorescence intensity and increased number of fluorescent cells ( Figure 7 b–f) showed that enhanced membrane permeability of Xoo cells occurred after incubation with compound 7c for 15 h when compared with the cells in the negative control ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%